2021
DOI: 10.1057/s41599-021-00871-1
|View full text |Cite
|
Sign up to set email alerts
|

Training wicked scientists for a world of wicked problems

Abstract: Humanity faces a number of wicked problems, from global climate change and the coronavirus pandemic to systemic racism and widening economic inequality. Since such complex and dynamic problems are plagued by disagreement among stakeholders over their nature and cause, they are notoriously difficult to solve. This commentary argues that if humanity truly aspires to address the grand challenges of today and tomorrow, then graduate education must be redesigned. It is no longer sufficient to train students only to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…These findings also serve as argumentational base in numerous publications (Barnett, 2018;e.g. Eisner, 2018;Forstmeier et al, 2017;Kawa et al, 2021;Kenna et al, 2017;Robson et al, 2021;Smaldino et al, 2019;Stewart & Plotkin, 2021). The study reported here attempts to replicate the agent-based model presented by Smaldino and McElreath (Smaldino & McElreath, 2016).…”
Section: Introductionmentioning
confidence: 89%
“…These findings also serve as argumentational base in numerous publications (Barnett, 2018;e.g. Eisner, 2018;Forstmeier et al, 2017;Kawa et al, 2021;Kenna et al, 2017;Robson et al, 2021;Smaldino et al, 2019;Stewart & Plotkin, 2021). The study reported here attempts to replicate the agent-based model presented by Smaldino and McElreath (Smaldino & McElreath, 2016).…”
Section: Introductionmentioning
confidence: 89%
“…These findings also serve as argumentational base in numerous publications (e.g. [3][4][5][6][7][8][9][10]). The study reported here attempts to replicate the agent-based model presented by Smaldino & McElreath [2].…”
Section: Introductionmentioning
confidence: 60%
“…In their article in this issue, Gigliotti and Spear share the importance of preparing students for a future of increasing uncertainty. In a poignant article on "Training Wicked Scientists for a World of Wicked Problems," Kawa et al (2021) observed that expertise in a given field is no longer sufficient. Instead, scientists must be adept at collaborating with a broad range of stakeholders.…”
Section: Tackling Wicked Problems Through Leadership Educationmentioning
confidence: 99%
“…As noted by Onyura et al (2019), "Leadership education needs to evolve to incorporate broader collective capacity building, as well as evidence-informed strategies for leadership development" (p. 133). Leadership educators cannot transform graduate and professional education without a clear focus on the skills and capacities that will facilitate solving today's most pressing complex and wicked problems (Kawa et al, 2021;Onyura et al, 2019). Historically, many view science as an individual pursuit, but there is increasing recognition that today's problems cannot be solved with a singular scientific answer, and team science has become a priority for funding agencies.…”
Section: Preparing Graduates For Leadershipmentioning
confidence: 99%